Efeito do treinamento resistido sobre o tecido cardíaco de ratos submetidos a dexametasona - Matos, Sandro Leão (2017)
Dexamethasone is a drug belonging to the class of corticosteroids, mostly used as an anti-inflammatory. In excess or in indiscriminate chronic use can lead to endocrine and / or cardiovascular complications. Physical exercise can act in the treatment of these diseases by acting as an attenuator or in some cases, reversing some of these complications, allied to traditional drug treatment. Thus, the purpose of this dissertation was: to evaluate the effect of a resistance exercise program on the heart and ventricles in animals submitted to dexamethasone treatment for four weeks. It was detected that aerobic or resistance training is capable of promoting improvements in patients in chronic use of glucocorticoids as a decrease in hyperglycemia, hypertension and improvements in cardiovascular indexes. For the experiments, forty male Wistar rats were selected and divided into four groups. The absolute heart and absolute and dry weight of the left and right ventricles were evaluated. It was verified that the strength exercise associated with dexamethasone (0.2 mg.kg-1.dia-1) did not significantly alter the absolute heart weight and absolute and dry weight of the right ventricle. There was a significant difference in the dry weight of the left ventricle that when normalized by the tibia length ceased to exist. This results suggest that exercise may be effective with some effects arising from the use of glucocorticoids and that four weeks of exercise associated with dexamethasone are not able to change the absolute and dry weight of the heart and ventricles.